Integrin‐Targeting Knottin Peptide–Drug Conjugates Are Potent Inhibitors of Tumor Cell Proliferation. (15th June 2016) - Cox, Nick; Kintzing, James R.; Smith, Mark; Grant, Gerald A.; Cochran, Jennifer R.
Abstract: Antibody–drug conjugates (ADCs) offer increased efficacy and reduced toxicity compared to systemic chemotherapy. Less attention has been paid to peptide–drug delivery, which has the potential for increased tumor penetration and facile synthesis. We report a knottin peptide–drug conjugate (KDC) and demonstrate that it can selectively deliver gemcitabine to malignant cells expressing tumor‐associated integrins. This KDC binds to tumor cells with low‐nanomolar affinity, is internalized by an integrin‐mediated process, releases its payload intracellularly, and is a highly potent inhibitor of brain, breast, ovarian, and pancreatic cancer cell lines. Notably, these features enable this KDC to bypass a gemcitabine‐resistance mechanism found in pancreatic cancer cells. This work expands the therapeutic relevance of knottin peptides to include targeted drug delivery, and further motivates efforts to expand the drug‐conjugate toolkit to include non‐antibody protein scaffolds.